(untitled) (Medical Forum Monthly, 2024)
Objectives: The main objectives of this study were to evaluate the complications of tracheostomy in IDPs patients who were admitted in DHQ teaching hospital Bannu and further the study of complications in relation with tracheostomy types, age and tracheostomy tubes types. Study Design: Observational / analytic / cross sectional study. Place and Duration of Study: The study was conducted at the ENT Unit, DHQ Teaching Hospital, Bannu from April 2015 to December 2015. Materials and Methods: 60 patients undergoing tracheostomy, having an age group of 3 to 65 and fulfilling inclusion and exclusion criteria were selected. Elective and emergency tracheostomy was included in the study period. “Open surgical technique” was done. Metallic and portex cuffed rubber tubes ware used. To record any possible complication, a pre-designed proforma was used. Results: The study comprised 42 males and 18 females. The mean age of the patients was 30 years(SD+18.20). Elective tracheostomy was done in 10% while emergency tracheostomy was done in rest of the 90% patients. Metallic tubes were used in 20% and portex cuffed rubber tubes in 80% of the patients. The recorded complication rate was 40% overall. There was an 18% immediate, 11% intermediate and 11% late complications. Complication rate was somewhat elevated in early age. Bleeding was commonest complication (20%) among all followed by emphysema, dysphagia and aspiration (4% each). Complication rate of emergency tracheostomy was higher than elective one. Similarly, complication rate with portex cuffed rubber tubes was greater than metallic tubes. Conclusion: Rate of complication in emergency tracheostomy was higher than elective tracheostomy where as in elder patients; it was lower than in younger patients. Similarly, complication rate was greater with portex cuffed rubber tubes. From the study, it is concluded that post op care can minimize the chances of post tracheostomy complications.